2012
DOI: 10.1111/j.1537-2995.2012.03780.x
|View full text |Cite
|
Sign up to set email alerts
|

How would I establish a perioperative blood salvage program?

Abstract: Nearly one‐quarter of the nation's blood supply is transfused to surgical patients. In many institutions, blood management programs that include autotransfusion (perioperative blood salvage) have been developed to decrease the need for allogeneic transfusion in eligible surgical patients. This article reviews management concepts related to an autotransfusion service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Finally, and in agreement with other authors, we found no difference between both groups in in-hospital mortality [13, 26,27]. We also found that the CS use has no impact on the rates of new onset renal impairment or infections, in line with the observed safety of the CS use by other authors [11,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, and in agreement with other authors, we found no difference between both groups in in-hospital mortality [13, 26,27]. We also found that the CS use has no impact on the rates of new onset renal impairment or infections, in line with the observed safety of the CS use by other authors [11,14].…”
Section: Discussionsupporting
confidence: 93%
“…The routine use of the CS is under continuous debate . Two recent meta‐analyses have concluded that the CS is effective in reducing transfusion needs .…”
Section: Discussionmentioning
confidence: 99%
“…The removal of platelets (PLTs), plasma proteins, and plasmatic coagulation factors may, however, enhance postoperative bleeding and homologous RBC or fresh‐frozen plasma (FFP) transfusion . The benefits of routine cell salvage as blood conservation technique during cardiac surgery are therefore still under debate, despite the increasing attention for standardized perioperative blood salvage programs …”
mentioning
confidence: 99%
“…Among the international publications are 3 instructive manuscripts in the category "How do I …?" that might be useful in the practical clinical support of blood and blood products during protracted humanitarian emergencies, provided blood and blood products are available (49)(50)(51). Natural -earthquake (n = 2), flooding (n = 4), drought (n = 1), landslide (n = 1), avalanche (n = 1), fire (n = 1) Human-made -terrorism (n = 10), war (including war in neighbouring countries) (n = 9), insurgency (n = 2), blockade (n = 2) These emergencies affect 20-100% of the community with estimated 10-85% of the injured requiring blood transfusion Need for blood transfusion has increased in all countries due to the humanitarian emergencies Type of emergencies has also changed over t he years -increasing conflicts and wars, explosions, acts of terrorism, refugees and population movements Emergencies affect both military personnel and civilians -women, men, children and old people.…”
Section: Literature Reviewmentioning
confidence: 99%